Estimación y control de leyes de producción mediante técnicas - Flores, Guillermo (2010)
This work aims seeks to achieve a suitable estimation and production control laws, using geostatistical technologies, to determine a reliable procedure of taking and preparation of detrituses of perforation generated in the quarry; as a correct interpolation method for the assignment of the law of a blast. The study area is located in the mining area CENACA to the Northwest of the city of Guayaquil; on the southern slope of the mountain chain Chongón-Colonche (is part of the Chongón-Colonche mountain range). For the development of research, we determined and quantified the mistake of sampling inside the current procedure of capture and preparation of sample, then setting the maximum sampling error based on production requirements, establish an appropriate procedure, then determined the best interpolation to estimate the percentage of SiO2 and SO3 a blast, using, the Mean Absolute Error (MAE) and the Mean Square Error (MSE) as precision measurements, also as a goodness of fit measurement, the prediction